2021
DOI: 10.22541/au.161912114.47713005/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide patterns of genetic diversity, population structure and demographic history in mānuka (Leptospermum scoparium) grown on indigenous Māori land

Abstract: Leptospermum scoparium J. R. Forst et G. Forst, known as mānuka by Māori, the indigenous people of Aotearoa (New Zealand), is a culturally and economically significant shrub species, native to New Zealand and Australia. Chemical, morphological and phylogenetic studies have indicated geographical variation of mānuka across its range in New Zealand, and genetic differentiation between New Zealand and Australia. We used pooled whole genome re-sequencing of 76 L. scoparium and outgroup populations from New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Quality filtering of the mānuka pooled sequencing datasets from Koot et al . [34] resulted in 2,006,036 SNPs. Eight classes of SNPs were identified based on their MAF values in each or a combination of gene pools (Northern North Island (NNI), the Central and Southern North Island (CNI), the East Coast North Island (ECNI), and two gene pools in the South Island representing the North-East (NESI) and South-West of the South Island (SWSI); S6 Table), and a total of 42,122 SNPs were identified that fitted into these classes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Quality filtering of the mānuka pooled sequencing datasets from Koot et al . [34] resulted in 2,006,036 SNPs. Eight classes of SNPs were identified based on their MAF values in each or a combination of gene pools (Northern North Island (NNI), the Central and Southern North Island (CNI), the East Coast North Island (ECNI), and two gene pools in the South Island representing the North-East (NESI) and South-West of the South Island (SWSI); S6 Table), and a total of 42,122 SNPs were identified that fitted into these classes.…”
Section: Resultsmentioning
confidence: 99%
“…Koot et al . [34] used pooled genome re-sequencing to study the genetic structure of mānuka collected across New Zealand. The SNP array data produced here for a subset of the populations described in Koot et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations